Kajian Pengembangan Kawasan Agropolitan Seroja Kabupaten Lumajang - Manik, Theodorik Rizal; Adrianto, Dimas Wisnu; Subagiyo, Aris (Jurnal Tata Kota dan Daerah, 2013)
Seroja’s Agropolitan Region is an economic’s strategic area of Lumajang Regency. Seroja’s Agropolitan Region development aims to develop agribusiness that environmentally sound, increase added value and competitiveness, leverage resources, increase household incomes and GDP, as well as re-positioning of marketing at the national and global. Based on this background, the purpose of this research was to identify the characteristics of the Seroja’s Agropolitan Region, determine the development of Seroja’s Agropolitan Region, and creates strategy and direction of Seroja’s Agropolitan Region development. The analysis uses descriptive method, policy analysis, economic potential analysis, suitability of land analysis, determination of commodities analysis, linkage system analysis, institutional analysis, participatory analysis, region evaluation of the agropolitan region concept analysis, the analysis of potential problems, and SWOT analysis. When viewed from the research results, there are 3 good commodities to be developed in Seroja’s Agropolitan Region that are banana commodity, durian commodity, and breadfruit commodity. Banana commodity in the implementation of the agribusiness system can be said to have run well and developed with government support. Durian commodity and breadfruit haven’t received support from the Regional Government of Lumajang Regency. Seroja’s Agropolitan Region sustainable development requires a strategy and direction such as development of appropriate sub-systems agrobusiness commodities, spatial direction of Seroja’s Agropolitan Region, development of conservation farming systems in the mountains, development of supporting infrastructure agropolitan, and human resource development.Keywords: Evaluation, Development, Agropolitan.